Literacy: State of the art at the tertiary level - Mullai Ramaiah (Journal of Modern Languages)
Malaysia is rapidly moving into an information-technology age in which full participation in education, science, business, industry and the professions is necessary and inevitable. The steady increase in the standards of literacy in the dynamic, social-economic environment must be met with. What seemed an adequate level of literacy in the 19805 seems marginal now. Hence, it is essential that tertiary level students attain a reasonable if not an excellent standard of literacy - literacy in English in particular, to meet the demands of the information era. Malaysia is rapidly moving into an information-technology age in which full participation in education, science, business, industry and the professions is necessary and inevitable. The steady increase in the standards of literacy in the dynamic, social-economic environment must be met with. What seemed an adequate level of literacy in the 19805 seems marginal now. Hence, it is essential that tertiary level students attain a reasonable if not an excellent standard of literacy - literacy in English in particular, to meet the demands of the information era.